Evaluating temperature variation of nutrient solution in Nutrient Film Technique (NFT) cooling system for temperate vegetable - Fazlil Ilahi, Wan Fazilah; Rosdi, Nur Syaffiqa Izleen; Ahmad Tajri, Azmi (Universiti Malaysia Kelantan, 2024)
The production of leafy green vegetables in hydroponic systems within greenhouses has gained global prominence in the fresh vegetable production industry. Hydroponic systems, particularly Nutrient Film Technique(NFT), are highly effective due to their soilless nature and efficient nutrient and water circulation. However, maintaining ideal greenhouse temperatures can be challenging. One strategy to reduce energy costs is to heat or cool the nutrient solution instead ofthe entire greenhouse environment. By regulating the root zone temperature through nutrient solution management, growers can provide more favourable conditions for temperate leafy greens. These conditions are critical because temperatures above 23°C can inhibit plant growth, while temperatures exceeding 35°C can significantly reduce plant metabolism efficiency. This study investigates how lettuce responds to nutrient solution cooling. Importantly, this research focuses on Malaysia, an equatorial country with a consistently warm and humid climate. In such environments, controlling nutrient solution or air temperature to match the crops' optimal growth requirements is crucial. The study employed Butterhead and Romaine lettuce varieties in a hydroponic NFT system. The EC (Environmental Cooling) treatment involved cooling the nutrient solution, while the RZC (Root Zone Cooling) treatment utilized environmental cooling. The results demonstrated that maintaining a consistent nutrient solution temperature within the range of 14°C to 18°C (as observed in the EC treatment) led to superior plant growth and quality, particularly in the early growth stages. In contrast, the RZC treatment showed temperature fluctuations, causing plant stress and inhibiting growth.